1990
DOI: 10.1164/ajrccm/141.5_pt_1.1114
|View full text |Cite
|
Sign up to set email alerts
|

Superior Vena Cava Syndrome: The Myth — the Facts

Abstract: This retrospective review was performed with an intent to clarify several misconceptions associated with superior vena cava syndrome (SVCS). During a 16-yr period, we diagnosed and treated 63 patients with SVCS, including seven (11%) children younger than 10 yr of age. Thirty patients (47.6%) had bronchogenic carcinoma, and 13 (20.6%) had lymphoma. In 43 cases SVCS was the presenting symptom of a mediastinal condition. Forty-one patients underwent diagnostic procedures with no major complications, and diagnosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
68
1
10

Year Published

1992
1992
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 161 publications
(81 citation statements)
references
References 7 publications
2
68
1
10
Order By: Relevance
“…However, we had one patient with diffuse bilateral adenocarcinoma and another in whom the primary growth was in the left lower lobe. The incidence of malignant thymoma in the present series is higher than in other series [5][6] but the explanation is not clear.…”
Section: Discussioncontrasting
confidence: 88%
See 1 more Smart Citation
“…However, we had one patient with diffuse bilateral adenocarcinoma and another in whom the primary growth was in the left lower lobe. The incidence of malignant thymoma in the present series is higher than in other series [5][6] but the explanation is not clear.…”
Section: Discussioncontrasting
confidence: 88%
“…This finding is similar to that reported earlier. Yellin [5] whereas Tayade et al reported that 89 per cent of cases were due to malignancy [6]. The commonest malignancy seen was bronchogenic carcinoma usually on the right side.…”
Section: Discussionmentioning
confidence: 99%
“…More than 80% of the cases result from malignant mediastinal tumors. In 75 -80% of cases, the underlying disease is bronchogenic carcinoma that is usually of small cell carcinoma type (2). A non-malignant cause of this syndrome can be the thrombosis resulting from intracaval catheters of pacemaker wire (3).…”
Section: Discussionmentioning
confidence: 99%
“…El SVCS es considerado por algunos grupos de trabajo como una verdadera emergencia 1,2 y otros lo consideran solo si presenta compromiso de la vía aérea superior o del sistema nervioso central, [3][4][5] pero en lo que sí coinciden es en que el diagnóstico etiológico es necesario para la toma de decisiones.…”
Section: Discussionunclassified